Employment Conditions in the Senegalese Horticultural Export Industry: A Worker Perspective. (2nd February 2016) - Van den Broeck, Goedele; Van Hoyweghen, Kaat; Maertens, Miet
Abstract : The rapid transformation of the agri‐food sector in developing countries has created rural off‐farm employment opportunities, especially for women. There is growing concern about worker welfare and employment conditions in agri‐food and export sectors, but empirical evidence on this issue is scant. We analyse contractual preferences of female workers in the horticultural export sector in Senegal. We use a discrete choice experiment to assess women's preferences for a labour contract and employ a latent class model to capture preference heterogeneity. We find that women have a high willingness to accept a labour contract in the horticultural export industry, and that differences in preferences for contract attributes can be explained by women's empowerment status.